Preparation method of hydrophobic electromagnetic shielding fabric with infrared stealth function
By bridging AgNWs with MXene nanosheets and spraying PFOTES, the problem that MXene cannot form an efficient conductive network on the fabric surface is solved, and the infrared stealth and electromagnetic shielding performance is improved, while maintaining the lightness and hydrophobicity of the fabric.
Patent Information
- Application Number
- CN202411571718.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, MXene is difficult to form a continuous conductive network due to irregular size after etching, resulting in infrared stealth and electrical conductivity decreases. Most fabrics that achieve infrared stealth and electromagnetic shielding are made of multi-layer coatings or multi-layer fabric stitching. This makes the overall thickness of the fabric larger.
By bridging one-dimensional AgNWs with MXene nanosheets with two-dimensional structural characteristics, an efficient conductive network is formed, and hydrophobic materials are obtained by spraying PFOTES, enhancing the hydrophobicity and electromagnetic shielding properties of the fabric.
It achieves excellent infrared stealth and electromagnetic shielding performance while keeping the fabric light, solving the problem that MXene cannot form an efficient continuous conductive network on the fabric surface, and improving the hydrophobicity of the fabric.
Smart Images

Figure CN119465623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of infrared stealth and electromagnetic shielding, and in particular to a method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function. Background Art
[0002] In recent years, with the rapid development of modern science and technology, electromagnetic waves have brought great convenience to human life, but also generated harmful electromagnetic interference (EMI). Therefore, the research on electromagnetic shielding materials is very important. With the advent of the era of intelligent sharing and human-computer interaction, wearable electronic devices have gradually entered people's field of vision. Electromagnetic shielding fabrics are an emerging, flexible, and lightweight electromagnetic shielding material that can be used in wearable, military and other fields. However, in modern warfare, detection technology is developing in the direction of intelligence, and infrared detectors can identify targets (target temperature is different from background temperature), which makes it difficult for electromagnetic shielding fabrics with single performance to meet practical applications. The detection range of infrared detectors is mainly concentrated in the 8-14 micron band. It highlights and identifies targets by capturing the heat signals emitted by objects in this band. According to the Stefan-Boltzmann law, reducing the emissivity and temperature of the target can achieve infrared stealth. Therefore, the development of electromagnetic shielding fabrics with excellent infrared stealth is very important to meet the requirements of complex practical applications.
[0003] Transition metal carbon / nitride (MXene) is an excellent electromagnetic shielding material due to its superior conductivity and rich surface functional groups. x -MXene has become an emerging infrared stealth material due to its inherent low mid- and far-infrared emissivity. x -MXene is difficult to form a continuous conductive network due to its irregular size after etching, resulting in infrared invisibility and decreased conductivity. Therefore, further improving the electromagnetic shielding efficiency of MXene to meet practical applications remains an urgent problem to be solved.
[0004] The Chinese invention patent with publication number CN115752095A discloses a multi-band-radar stealth-compatible multifunctional camouflage net and its preparation method. It uses high-strength flame-retardant polyester as the base material, and is coated with visible light-infrared composite stealth coating in conjunction with screen printing technology or coating technology to prepare a composite stealth coating fabric with multi-band camouflage stealth function. Another Chinese utility model patent with publication number CN213663747U discloses an anti-electromagnetic radiation clothing that is convenient for infrared stealth. The top of the fabric layer is tightly fitted with infrared stealth fabric, and the bottom of the infrared stealth fabric is tightly fitted with anti-electromagnetic radiation fabric, which can reflect and shield electromagnetic radiation. It is worth noting that the current research on the use of MXene to prepare infrared stealth and electromagnetic shielding coated fabrics is relatively rare, and most of the fabrics that achieve infrared stealth and electromagnetic shielding now use multi-layer coatings or multi-layer fabric stitching, which makes the overall thickness of the fabric larger.
[0005] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention
[0006] The present invention overcomes the shortcomings of the prior art and provides a method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function. The primary problem solved is to utilize the low emissivity and conductivity of MXene to give the fabric infrared stealth and electromagnetic shielding performance.
[0007] Secondly, due to the irregular size of MXene after etching, it is difficult to form a continuous conductive network, resulting in a decrease in conductivity. Therefore, further improving the electromagnetic shielding efficiency and infrared stealth performance of MXene to meet practical applications is still an urgent problem that needs to be solved.
[0008] Finally, the effect of the amount of AgNWs used on the infrared stealth and electromagnetic shielding properties of MXene@AgNWs fabrics was studied, and a series of flexible, hydrophobic MXene@AgNWs electromagnetic shielding fabrics with infrared stealth were obtained by spraying PFOTES.
[0009] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function, comprising the following steps:
[0010] S1, ultrasonically immersing the fabric in anhydrous ethanol, washing with water, soaking in an alkaline solution, washing with water and drying to obtain a pretreated fabric;
[0011] S2, reducing silver nitrate by a reducing agent to obtain an AgNWs aqueous solution;
[0012] S3, etching the MAX phase material to obtain a MXene dispersion;
[0013] S4, mixing the AgNWs aqueous solution in step S2 and the MXene dispersion in step S3 in a certain proportion, cutting the fabric pretreated in step S1 into discs, placing them on a vacuum suction filter bottle, repeating vacuum-assisted suction filtration, and drying in a vacuum oven to obtain MXene@AgNW / fabric;
[0014] S5. Spray a hydrophobic material onto the surface of the MXene@AgNW / fabric in step S4 to obtain a hydrophobic MXene@AgNW / cotton fabric.
[0015] In a preferred embodiment of the present invention, in step S1, the fabric is one of cotton fabric, polyester fabric or aramid fabric; and the thickness of the fabric is 1 to 3 mm.
[0016] In a preferred embodiment of the present invention, in step S1, the power of the ultrasound is 5-30% and the time is 5-30 minutes.
[0017] In a preferred embodiment of the present invention, in step S1, the alkaline solution is one of sodium hydroxide or potassium hydroxide; the concentration of the alkaline solution is 10 to 20 g / L; and the soaking time is 4 to 12 hours.
[0018] In a preferred embodiment of the present invention, in step S2, the reducing agent is one of glycine, polyethyleneimine or glucose.
[0019] In a preferred embodiment of the present invention, in the step S3, the MXene is etched by one of HF, NH4HF2 or LiF+HCl.
[0020] In a preferred embodiment of the present invention, in step S3, the MXene is Ti3C2T x 、Ti2CT x 、Ti3CNT x or V2CT x One of them.
[0021] In a preferred embodiment of the present invention, in the step S4, the mass ratio of the AgNWs aqueous solution to the MXene dispersion is 1 to 3:1.
[0022] In a preferred embodiment of the present invention, in the step S4, the number of vacuum-assisted suction filtration is 8 to 12 times; the drying temperature is 60 to 100° C., and the drying time is 2 to 4 hours.
[0023] In a preferred embodiment of the present invention, in step S5, the hydrophobic material is one of polytetrafluoroethylene, polypropylene or PFOTES.
[0024] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0025] (1) The present invention provides a method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function. By bridging one-dimensional AgNWs with MXene nanosheets having two-dimensional structural characteristics, the gaps in the MXene nanosheets can be bridged, providing a more continuous and effective path for the transmission of charges within the MXene nanosheets. The bridging effect can form an efficient conductive network. When electromagnetic waves contact the coating, they will be absorbed, reflected or scattered by the free charges provided by AgNWs and MXene in the fabric, thereby effectively reducing the penetration of electromagnetic waves and improving the electromagnetic shielding performance. At the same time, MXene itself has a low infrared emissivity. The introduction of AgNWs not only improves its conductivity, but also affects the absorption and reflection characteristics of the fabric to infrared radiation, so that the fabric can better hide its own infrared characteristics. Therefore, under the synergistic effect of the combination of AgNWs and MXene, the fabric has excellent infrared stealth and electromagnetic shielding performance while maintaining its lightness.
[0026] (2) In the present invention, by precisely controlling the content of AgNWs, the infrared stealth and electromagnetic shielding effectiveness of the fabric composite material can be effectively improved, solving the problem that a single MXene cannot form an efficient and continuous conductive network on the fabric surface, thereby increasing the infrared emissivity and decreasing the electrical conductivity.
[0027] (3) In the present invention, by spraying PFOTES, which has an extremely low surface energy, and the fluorine atoms contained in it can form a strong hydrophobic barrier, react with the functional groups on the surface of MXene to form chemical bonds, which not only enhances the binding force between PFOTES and MXene, but also makes the surface of the MXene layer covered with a fluorinated layer with extremely high hydrophobicity. Water molecules are effectively blocked outside the MXene layer, reducing the chance of reaction between water molecules and MXene. In addition, the strong electronegativity of fluorine atoms can also attract and fix the surrounding electrons to a certain extent, forming a layer of electron cloud barrier, further blocking the entry and reaction of oxygen molecules, so that the hydrophobically modified fabric composite material has higher electromagnetic shielding efficiency and better infrared stealth effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 MXene5@AgNWs in Example 1 of the present invention 1.16 / Actual picture and SEM morphology of cotton fabric;
[0030] Figure 2 The cotton fabric and MXene5@AgNWs in Example 1 of the present invention 1.16 / Infrared image of cotton fabric on a hot stage at 200℃;
[0031] Figure 3 MXene5@AgNWs in Example 1 of the present invention 1.16 / Hydrophobic angle test chart of cotton fabric after spraying PFOTES. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0034] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.
[0035] A method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function comprises the following steps:
[0036] S1, ultrasonically immersing the fabric in anhydrous ethanol, washing with water, soaking in an alkaline solution, washing with water and drying to obtain a pretreated fabric;
[0037] S2, reducing silver nitrate by a reducing agent to obtain an AgNWs aqueous solution;
[0038] S3, etching the MAX phase material to obtain a MXene dispersion;
[0039] S4, mixing the AgNWs aqueous solution in step S2 and the MXene dispersion in step S3 in a certain proportion, cutting the fabric pretreated in step S1 into discs, placing them on a vacuum suction filter bottle, repeating vacuum-assisted suction filtration, and drying in a vacuum oven to obtain MXene@AgNW / fabric;
[0040] S5. Spray a hydrophobic material onto the surface of the MXene@AgNW / fabric in step S4 to obtain a hydrophobic MXene@AgNW / cotton fabric.
[0041] In some specific embodiments, in step S1, the fabric is one of cotton fabric, polyester fabric or aramid fabric; the thickness of the fabric is 1 to 3 mm; the power of ultrasound is 5 to 30%, and the time is 5 to 30 min; the alkaline solution is one of sodium hydroxide or potassium hydroxide; the concentration of the alkaline solution is 10 to 20 g / L; and the immersion time is 4 to 12 h.
[0042] In a preferred embodiment, the fabric is cotton fabric with a thickness of 1.5 mm; the ultrasonic power is 10% and the time is 20 min; the alkaline solution is NaOH with a concentration of 15 g / L; and the soaking time is 8 h.
[0043] In some specific embodiments, in step S2, the reducing agent is one of glycine, polyethyleneimine or glucose.
[0044] In a preferred embodiment, the reducing agent is glucose.
[0045] In some specific embodiments, in step S3, MXene is etched by one of HF, NH4HF2 or LiF+HCl; MXene is Ti3C2T x 、Ti2CT x 、Ti3CNT x or V2CT x One of them.
[0046] In a preferred embodiment, MXene is etched by LiF+HCl; MXene is Ti3C2T x .
[0047] Among them, in step S2, the MAX phase is a layered structure material composed of Mn+1AXn (M is an early transition metal, A is a IIIA or IVA group element, and X is carbon or nitrogen). The name of MXene comes from the MAX phase, where "M" represents an early transition metal, "X" represents carbon or nitrogen, and "ene" indicates that it is a two-dimensional material. Since the MX bond has a strong bond energy and the A element has a more active chemical activity, the A element can be removed from the MAX phase through an etching process to obtain a graphene-like two-dimensional structure - MXene.
[0048] In some specific embodiments, in step S4, the mass ratio of the AgNWs aqueous solution to the MXene dispersion is 1 to 3:1; the number of vacuum-assisted filtration is 8 to 12 times; the drying temperature is 60 to 100° C., and the time is 2 to 4 hours.
[0049] In a preferred embodiment, the mass ratio of the AgNWs aqueous solution to the MXene dispersion is 2:1; the number of vacuum-assisted filtration is 10 times; the drying temperature is 80°C and the drying time is 3 hours.
[0050] In some specific embodiments, in step S5, the hydrophobic material is one of polytetrafluoroethylene, polypropylene or PFOTES.
[0051] In a preferred embodiment, the hydrophobic material is PFOTES.
[0052] Example 1
[0053] A method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function comprises the following steps:
[0054] S1. Soak a cotton fabric with a thickness of 0.15 mm in anhydrous ethanol at an ultrasonic power of 10% for 20 min, then wash it with water, then soak the fabric in a 15 g / L NaOH aqueous solution for 8 h, wash it with water and dry it to obtain a pretreated cotton fabric;
[0055] S2, dissolving 0.226g AgNO3 in 66.6mL water to obtain solution A, dissolving 0.156g NaCl in 13.32mL water to obtain solution B, slowly adding solution B to solution A, adding 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL); hydrothermally reacting the above mixed solution at 160°C in a reactor for 24h, centrifuging 6 times, collecting the AgNWs aqueous solution, and adjusting the concentration of the AgNWs aqueous solution to obtain an AgNWs aqueous solution with a concentration of 1.16mg / mL;
[0056] S3, take 20mL of 9M HCl solution and pour it into a polytetrafluoroethylene beaker, weigh 1.6g LiF and add it to the beaker, stir for 5min to obtain an etching solution, slowly add 1g of Ti3AlC2 powder to the above-configured etching solution several times, and continue to react at 38°C (with magnetic stirring) for 48 hours, then centrifuge and wash the multilayer MXene dispersion obtained after the reaction in water several times until the pH is 7, finally ultrasonically treat the multilayer MXene dispersion for 60min, and centrifuge for 30min to obtain a few-layer MXene dispersion with a concentration of 5mg / mL;
[0057] S4, 40 mL of MXene dispersion was uniformly mixed with 20 mL of AgNWs aqueous solution, and magnetic stirring was performed for 30 min. The pretreated cotton fabric was cut into a disc with a diameter of 5 cm and placed on a vacuum suction filter bottle. The cotton fabric was vacuum-assisted suction filtered 10 times and dried in a vacuum oven at 80 °C for 3 h to obtain MXene5@AgNWs. 1.16 / cotton fabric;
[0058] In order to verify the successful acquisition of MXene5@AgNWs in Example 1 1.16 / cotton fabric, Figure 1 Shown as MXene5@AgNWs in Example 1 1.16 The physical picture and SEM morphology of the cotton fabric show that the flexible AgNWs with high aspect ratio play the role of connecting adjacent MXene nanosheets, and build a continuous and efficient three-dimensional interconnected conductive network on the cotton fabric substrate, which is similar to the nutrients transported from the ground to the trunk through the roots, enhancing the conductivity, electromagnetic shielding and infrared stealth performance of the composite fabric; MXene5@AgNWs were tested using a vector network analyzer 1.16 / Electromagnetic shielding performance of cotton fabric, the results show that its thickness is 1.583mm and the coating mass is 9.2mg / cm 2 The electromagnetic shielding effectiveness value of MXene5@AgNWs at 8.2-12.4 GHz is 70.6 dB. 1.16 The infrared emissivity of MXene5@AgNWs / cotton fabric was tested. Table 1 shows the infrared emissivity of MXene5@AgNWs in Example 1. 1.16 The infrared emissivity of MXene5@AgNWs / cotton fabrics in the range of 3-5 μm and 8-14 μm respectively. 1.16 The average emissivity of MXene5@AgNWs in the range of 3-5 μm and 8-14 μm was 0.25 and 0.17, respectively. 1.16 / Temperature change of cotton fabric placed on a hot table, Figure 2 The cotton fabric and MXene5@AgNWs in Example 1 are shown 1.16 / Infrared image of cotton fabric on a 200℃ hot stage. The surface temperature of the cotton fabric placed on a 200℃ hot stage is 130℃. MXene5@AgNWs 1.16 / cotton fabric is only 67.8℃, proving that MXene5@AgNWs 1.16 / Cotton fabric can effectively reduce the emission of infrared light and has infrared stealth capability.
[0059] Table 1:
[0060] Sample name 3~5μm infrared emissivity 8~14μm infrared emissivity <![CDATA[MXene5@AgNWs 1.16 / cotton fabric]]> 0.25 0.17
[0061] S5. Prepare 70 mL of 1% PFOTES ethanol solution and spray the PFOTES ethanol solution on the MXene5@AgNWs obtained in step S4. 1.16 / cotton fabric surface, dried to obtain P-MXene5@AgNWs 1.16 / cotton fabric.
[0062] Contact angle meter was used to test P-MXene5@AgNWs 1.16 / Hydrophobicity of cotton fabrics, Figure 3 It shows that MXene5@AgNWs in Example 1 1.16 / The hydrophobic angle test diagram of cotton fabric after spraying PFOTES. The results show that surface modification, reduction of surface free energy, and construction of hydrophobic surface P-MXene5@AgNWs 1.16 / cotton fabric, the hydrophobic angle is 135.1°, proving that PFOTES-modified MXene5@AgNWs 1.16 / Cotton fabric has good hydrophobicity.
[0063] Example 2
[0064] This embodiment is basically the same as embodiment 1, except that: step S2 is as follows: 0.226g AgNO3 is dissolved in 66.6mL water to obtain solution A, 0.156g NaCl is dissolved in 13.32mL water to obtain solution B, solution B is slowly added to solution A, and 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL) is added; the mixed solution is hydrothermally reacted at 160℃ in a reactor for 24h, centrifuged 6 times, the AgNWs aqueous solution is collected, and the concentration of the AgNWs aqueous solution is adjusted to obtain an AgNWs aqueous solution with a concentration of 1.11mg / mL. P-MXene5@AgNWs is prepared 1.11 / cotton fabric.
[0065] Example 3
[0066] This embodiment is basically the same as embodiment 1, except that: step S2 is as follows: 0.226g AgNO3 is dissolved in 66.6mL water to obtain solution A, 0.156g NaCl is dissolved in 13.32mL water to obtain solution B, solution B is slowly added to solution A, and 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL) is added; the mixed solution is hydrothermally reacted at 160℃ in a reactor for 24h, centrifuged 6 times, the AgNWs aqueous solution is collected, and the concentration of the AgNWs aqueous solution is adjusted to obtain an AgNWs aqueous solution with a concentration of 1.24mg / mL. P-MXene5@AgNWs is prepared 1.24 / cotton fabric.
[0067] Example 4
[0068] This embodiment is basically the same as embodiment 1, except that: step S2 is as follows: 0.226g AgNO3 is dissolved in 66.6mL water to obtain solution A, 0.156g NaCl is dissolved in 13.32mL water to obtain solution B, solution B is slowly added to solution A, and 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL) is added; the mixed solution is hydrothermally reacted at 160℃ in a reactor for 24h, centrifuged 6 times, the AgNWs aqueous solution is collected, and the concentration of the AgNWs aqueous solution is adjusted to obtain an AgNWs aqueous solution with a concentration of 0.96mg / mL. P-MXene5@AgNWs is prepared 0.96 / cotton fabric.
[0069] Example 5
[0070] This embodiment is basically the same as embodiment 1, except that: step S2 is as follows: 0.226g AgNO3 is dissolved in 66.6mL water to obtain solution A, 0.156g NaCl is dissolved in 13.32mL water to obtain solution B, solution B is slowly added to solution A, and 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL) is added; the mixed solution is hydrothermally reacted at 160℃ in a reactor for 24h, centrifuged 6 times, the AgNWs aqueous solution is collected, and the concentration of the AgNWs aqueous solution is adjusted to obtain an AgNWs aqueous solution with a concentration of 0.89mg / mL. P-MXene5@AgNWs is prepared 0.89 / cotton fabric.
[0071] Example 6
[0072] This embodiment is basically the same as embodiment 1, except that: step S2 is as follows: 0.226g AgNO3 is dissolved in 66.6mL water to obtain solution A, 0.156g NaCl is dissolved in 13.32mL water to obtain solution B, solution B is slowly added to solution A, and 400mL glucose aqueous solution (the concentration of glucose is 1.17mg / mL) is added; the mixed solution is hydrothermally reacted at 160℃ in a reactor for 24h, centrifuged 6 times, the AgNWs aqueous solution is collected, and the concentration of the AgNWs aqueous solution is adjusted to obtain an AgNWs aqueous solution with a concentration of 1.28mg / mL. P-MXene5@AgNWs is prepared 1.28 / cotton fabric.
[0073] Example 7
[0074] This embodiment is basically the same as embodiment 1, except that: step S5 is to prepare 70 mL of 0.7% PFOTES ethanol solution, and spray the PFOTES ethanol solution on the MXene5@AgNWs obtained in step S4. 1.16 / cotton fabric surface, dried to obtain P-MXene5@AgNWs 1.16 / cotton fabric.
[0075] Example 8
[0076] This embodiment is basically the same as embodiment 1, except that: step S5 is to prepare 70 mL of 0.5% PFOTES ethanol solution, and spray the PFOTES ethanol solution on the MXene5@AgNWs obtained in step S4. 1.16 / cotton fabric surface, dried to obtain P-MXene5@AgNWs 1.16 / cotton fabric.
[0077] Example 9
[0078] This embodiment is basically the same as embodiment 1, except that: step S5 is to prepare 70 mL of 1.4% PFOTES ethanol solution, and spray the PFOTES ethanol solution on the MXene5@AgNWs obtained in step S4. 1.16 / cotton fabric surface, dried to obtain P-MXene5@AgNWs 1.16 / cotton fabric.
[0079] Example 10
[0080] This embodiment is basically the same as embodiment 1, except that: step S5 is to prepare 70 mL of 1.9% PFOTES ethanol solution, and spray the PFOTES ethanol solution on the MXene5@AgNWs obtained in step S4. 1.16 / cotton fabric surface, dried to obtain P-MXene5@AgNWs 1.16 / cotton fabric.
[0081] Comparative Example 1
[0082] This comparative example is basically the same as Example 1, except that there is no S2 step. The S4 step is specifically to cut the pretreated cotton fabric into discs with a diameter of 5 cm, place them on a vacuum suction filter bottle, repeat the vacuum-assisted suction filtration of 40 mL of MXene dispersion on the cotton fabric 10 times, and dry it in a vacuum oven at 80°C for 3 h to obtain P-MXene5 / cotton fabric.
[0083] Comparative Example 2
[0084] This comparative example is basically the same as Example 1, except that there is no S5 step, and MXene5@AgNWs is obtained. 1.16 / cotton fabric.
[0085] Performance test: The fabrics obtained in the above embodiments 2-10 and comparative examples 1-2 were first tested on a hot table at 200°C with an infrared thermal imager to detect the surface temperature; the electromagnetic shielding performance of the fabrics at 8.2-12.4 GHz was then tested with a vector network analyzer; and the antioxidant capacity (DPPH free radical scavenging rate was an indicator) was tested; finally, the electromagnetic shielding performance of the fabrics after antioxidant treatment at 8.2-12.4 GHz was tested with a vector network analyzer, and compared with that in Example 1. The results are shown in Table 2.
[0086] The specific steps of the antioxidant capacity test are as follows: 80 mL of 50% ethanol solution by volume and 20 mL of DPPH·ethanol solution (0.1 mmol / L) are mixed to obtain a DPPH test solution. The fabrics obtained in Examples 1-10 and Comparative Examples 1-2 are placed in the DPPH test solution respectively, and the absorbance A0 is detected at this time. The fabrics are heated in a shaking water bath at 37°C in a light-proof environment for 0.5 h, and the absorbance A1 is detected at this time. The DPPH test solution is heated in a shaking water bath at 37°C in a light-proof environment for 0.5 h, and the absorbance A2 is detected at this time. According to the formula, The DPPH free radical scavenging rate of the fabric was obtained.
[0087] Table 2:
[0088]
[0089] As shown in Table 2, by comparing Example 1 with Comparative Example 1, it can be learned that by bridging one-dimensional AgNWs with MXene nanosheets having two-dimensional structural characteristics, the gaps in the MXene nanosheets can be bridged, providing a more continuous and effective path for the transmission of charges within them, and the bridging effect can form an efficient conductive network. When electromagnetic waves contact the coating, they will be absorbed, reflected or scattered by the free charges provided by AgNWs and MXene in the fabric, thereby effectively reducing the penetration of electromagnetic waves and improving the electromagnetic shielding performance. At the same time, MXene itself has a low infrared emissivity. The introduction of AgNWs not only improves the conductivity of the fabric, but also affects the absorption and reflection characteristics of the fabric for infrared radiation, so that the fabric can better hide its own infrared characteristics. Therefore, under the synergistic effect of the combination of AgNWs and MXene, the fabric has excellent infrared stealth and electromagnetic shielding properties while maintaining lightness.
[0090] By comparing Example 1 with Examples 2-6, it can be seen that precisely controlling the content of AgNWs can effectively improve the infrared stealth and electromagnetic shielding effectiveness of the fabric composite material, and solve the problem that a single MXene cannot form an efficient and continuous conductive network on the fabric surface, thereby increasing the infrared emissivity and decreasing the electrical conductivity. When the content is too low, the conductive network in the fabric composite material is not perfect, resulting in obstruction of the transmission path of electromagnetic waves, and failure to form an effective electromagnetic shielding layer, making it easier for electromagnetic waves to penetrate the material. If the content is too high, excessive conductivity will be formed, which will limit the entry of electromagnetic waves into the interior of the shield due to the impedance mismatch at the interface between the air and the shielding material, thereby increasing reflection losses, thereby reducing shielding effectiveness and indirectly affecting the infrared stealth effect.
[0091] By comparing Example 1 with Comparative Example 2, it can be learned that by spraying PFOTES, it has extremely low surface energy, and the fluorine atoms it contains can form a strong hydrophobic barrier, which will react with the functional groups on the surface of MXene to form chemical bonds, which not only enhances the binding force between PFOTES and MXene, but also makes the surface of the MXene layer covered with a fluorinated layer with extremely high hydrophobicity, and water molecules are effectively blocked outside the MXene layer, reducing the chance of reaction between water molecules and MXene, and the strong electronegativity of fluorine atoms can also attract and fix the surrounding electrons to a certain extent, forming a layer of electron cloud barrier, further blocking the entry and reaction of oxygen molecules, so that the hydrophobically modified fabric composite material has higher electromagnetic shielding efficiency and better infrared stealth effect.
[0092] By comparing Example 1 with Examples 7-10, it can be seen that an appropriate PFOTES content can reduce the oxidation of the MXene layer and increase the hydrophobic properties of the fabric. When the content is too low, the hydrophobic layer formed on the surface of the MXene layer is not dense or uniform enough, which makes the MXene layer more susceptible to oxidative damage, thereby affecting its electrical conductivity and structural integrity. When the content is too high, it is easy to cause agglomeration or defects to form on the surface of the MXene layer, and cause the interface bonding force between the MXene layer and AgNWs or fabric to weaken, becoming a channel for water molecules and oxygen molecules to penetrate, thereby weakening the electromagnetic shielding effectiveness.
[0093] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0094] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function, characterized in that: The following steps are involved: S1, ultrasonically immersing the fabric in anhydrous ethanol, washing with water, soaking in an alkaline solution, washing with water and drying to obtain a pretreated fabric; S2, reducing silver nitrate by a reducing agent to obtain an AgNWs aqueous solution; S3, etching the MAX phase material to obtain a MXene dispersion; S4, mixing the AgNWs aqueous solution in step S2 and the MXene dispersion in step S3 in a certain proportion, cutting the fabric pretreated in step S1 into discs, placing them on a vacuum suction filter bottle, repeating vacuum-assisted suction filtration, and drying in a vacuum oven to obtain MXene@AgNW / fabric; S5. Spray a hydrophobic material onto the surface of the MXene@AgNW / fabric in step S4 to obtain a hydrophobic MXene@AgNW / cotton fabric.
2. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In step S1, the fabric is one of cotton fabric, polyester fabric or aramid fabric; and the thickness of the fabric is 1 to 3 mm.
3. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S1, the power of the ultrasound is 5-30% and the time is 5-30 minutes.
4. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In step S1, the alkaline solution is one of sodium hydroxide and potassium hydroxide; the concentration of the alkaline solution is 10 to 20 g / L; and the soaking time is 4 to 12 hours.
5. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In step S2, the reducing agent is one of glycine, polyethyleneimine or glucose.
6. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S3, the MXene is etched by one of HF, NH4HF2 or LiF+HCl.
7. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S3, the MXene is Ti3C2T x 、Ti2CT x 、Ti3CNT x or V2CT x One of them.
8. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S4, the mass ratio of the AgNWs aqueous solution to the MXene dispersion is 1 to 3:
1.
9. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S4, the vacuum-assisted filtration is performed 8 to 12 times; the drying temperature is 60 to 100° C., and the drying time is 2 to 4 hours.
10. The method for preparing a hydrophobic electromagnetic shielding fabric with infrared stealth function according to claim 1, characterized in that: In the step S5, the hydrophobic material is one of polytetrafluoroethylene, polypropylene or PFOTES.
Citation Information
Patent Citations
Multiband-radar stealth compatible multifunctional camouflage net and preparation method thereof
CN115752095A
Anti-electromagnetic radiation garment facilitating infrared stealth
CN213663747U
Fabric material and production method thereof
CN110438799A
Flexible high-strength MXene-based electromagnetic shielding composite film and preparation method thereof
CN111809439A
Electromagnetic shielding composite film for new energy automobile and preparation method of electromagnetic shielding composite film
CN118849560A